Aqueous-Phase Selective Oxidation of Methane with Oxygen over Iron Salts and Pd/C in the Presence of Hydrogen - Kang, Jongkyu; Park, Eun Duck (ChemCatChem, 2019)
Direct conversion of methane into value-added chemicals is a challenging but worthwhile subject. In this communication, the direct conversion of methane into methane oxygenates was achieved in an aqueous solution at room temperature using iron salts and Pd/C as catalysts and hydrogen peroxide as an oxidant. The hydrogen peroxide can be directly added or generated in situ from hydrogen and oxygen. The Pd/C catalyst greatly enhanced the reaction rate together with the iron salts. The effect of some parameters such as reaction temperature, reaction time, pH, acid type, and catalyst amount on the yields of the methane oxygenates was also investigated. When hydrogen peroxide was directly added, the turnover frequency (TOF), defined as the moles of methane oxygenates per moles of Fe per unit time, at 293 K was 29 h−1 at pH=2.3. The TOF at 293 K was 42 h−1 at pH=1.3 with in situ generated hydrogen peroxide from hydrogen and oxygen.
Keywords: Direct conversion; Fenton chemistry; Pd catalyst; Pd/C catalyst; Reaction temperature; Selective oxidation; Turnover frequency; Value-added chemicals; Fenton chemistry; Formic acid; methane; oxidation; Pd catalyst